Impact of Social Media Marketing on Brand Equity : Case Study of Samsung Smartphones in Azerbaijan - Rasulov, Eldar (ADA University, 2021)
The research aimed to analyze the relationship between social media marketing (SMM) and brand equity (BE) from customers’ perspective. In this regard, the research assessed the impact of SMM on four dimensions of BE in case Samsung smartphones in Azerbaijan, which included brand awareness, brand image, brand loyalty and perceived quality. The review of existing researches on the research topic revealed that the SMM is one of the significant determinants of the BE of goods or services in the current business environment due to its impact on different dimensions of the brand equity. Accordingly, it was expected to identify the positive and empirically significant relationships between SMM and BE in case of Samsung smartphones in Azerbaijan from the viewpoints of customers. In this regard, the primary data about SMM and BE of Samsung smartphones in Azerbaijan was collected from the sample of 148 social media users who possessed Samsung smartphones at the time of data collection for this study. The sample of target population was built through snowball non-probability sampling method in this research. The obtained data about SM and BE of Samsung smartphones in Azerbaijan was assessed through three analysis methods, like descriptive statistics, Cronbach’s alpha and regression analysis. In this research, there were four regression models developed for determining the predictors of each of four dimensions of BE in case of Samsung smartphones in Azerbaijan. The data analysis process in the study was conducted at one of the most commonly used statistics software in social science, Statistical Package for the Social Sciences (SPSS). The research findings revealed that the channels of SMM are statistically significant predictors of the changes in the dimensions of BE for Samsung smartphones in Azerbaijan. In particular, the interpretation of primary data in the research highlighted that SMM has statistically significant and positive impact of BE of Samsung smartphones in Azerbaijan. Thus, the research concluded that the relationship between SMM and BE was statistically significant and positive from the perspective of customers of Samsung smartphones in Azerbaijan.
Keywords: Social Media Marketing.; Brand Equity.; Brand Exposure.; Brand Engagement.; Brand Awareness.; Brand Image.; Brand Loyalty.; Perceived Quality.; Business